Vector fields generating more than one flow - Slawomir Dorosiewicz; Kazimierz Napiórkowski (International Journal of Mathematics and Mathematical Sciences)
Vector fields generating more than one flow on a manifold are constructed. For one-dimensional case a complete description of the set of flows is given. For dimensions larger than one a method of constructing vector fields with dense or open branched sets sets is given. Density of vector fields with nonempty sets of branched points is studied.